Domestication, fertilization, and induced defenses modulate tomato plant resistance to Tuta absoluta - Salazar Mendoza, Paolo Salvatore (2023)
Tomato (Solanum lycopersicum L.) is a globally important vegetable crop, but its production faces challenges due to the presence of pests. Among these, the South American tomato pinworm Tuta absoluta stands out as a highly destructive insect pest, causing significant losses in tomato yields worldwide The reliance on synthetic chemical insecticides for pest control has led to concerns about environmental impact and the development of insecticide resistance. Therefore, alternative sustainable management strategies, such as enhancing plant resistance are being sought. This thesis aims to address several key questions related to tomato resistance mechanisms and their potential in the management of T. absoluta. Firstly, we investigated the impact of domestication on the loss of defensive traits in a modern tomato variety compared to its wild ancestors, and how these changes could explain variations in susceptibility to T. absoluta. Secondly, we explored the potential of using the endophytic fungus Metarhizium robertsii, either alone or in combination with the rhizobacterium Bacillus amyloliquefaciens, for the protection of both wild and cultivated tomato plants to reduce T. absoluta attacks while also attracting its natural enemy for biological control. Lastly, we investigated the influence of fertilization and jasmonate- induced resistance on defensive traits in cultivated tomatoes, and also determined how these factors impact the resistance of tomato plants against T. absoluta. Our findings reveal that cultivated tomatoes have reduced their defensive traits while enhancing nutritional quality, making them more susceptible to T. absoluta. However, the defensive mechanisms of both wild and cultivated tomatoes to reduce the preference of T. absoluta and attract its natural enemy can be strengthened through inoculations with M. robertsii alone or in combination with B. Amyloliquefaciens.Additionally, applications of MeJA were observed to enhance defensive traits, resulting in increased resistance against T. absoluta. Conversely, plants subjected to high levels of fertilization exhibited increased susceptibility to T. absoluta preference and performance. Our findings provide valuable insights into improving tomato resistance through the identification of defensive traits from wild counterparts, and the manipulation of plant nutritional status and induced defenses by beneficial microbes and jasmonates.